An optimized CFD-DEM method for fluid-particle coupling dynamics analysis - Yao, L. M. (2021)
When the unresolved CFD-DEM (Computational Fluid Dynamics and Discrete Element Method) method is used to solve two-phase flow (composed of fracturing fluid and quartz sand) problems in a pipe, although the collision and accumulation of particles can be described in mesoscopic scale, the method has a serious shortcoming: the contradiction between computational efficiency and computational accuracy. In the current study, an improved CFD-DEM method based on time roundabout increment way is proposed. By improving the solution strategy of unresolved CFD-DEM in terms of time incremental way, the iterative convergence criteria and time advancement algorithm of fluid-particle coupling have been established. The improved CFD-DEM method can automatically adjust the CFD time steps according to the convergence criteria. At each time step, the particle iteration updates the force between the fluid and the particle. Also the fluid can be solved in a roundabout way based on the convergence criteria. A computational example is given by applying the improved CFD-DEM method to analyze a two-phase flow (fracturing fluid and quartz sand) in a contraction-expansion pipe. The result shows that the new method can simulate particle collisions efficiently, and calculate the pressure loss of the two-phase flow accurately. It is found that when the sand ratio is increased from 0 to 56%, the accumulation of particles at the outer edge of the sudden contraction/expansion section is more pronounced, while the force chain is much easier to be formed. When the diameter ratio increases from 0.3 to 0.7, the particle accumulation is weakened and the particle collision force chain is evenly distributed. Our research work provides a highly effective computational method for the solution of solid-liquid two-phase flow, and can be applied for coupled dynamic analysis of particles and fluids.